LABORATORY STUDY TO DETERMINE THE EFFICIENCY OF PREDATION OF Chrysoperla mutata MACL. TO DUBAS NYMPHS Ommatissus lybicus .DeBberg. - حمد باسم; الراوي محمد (Iraqi Journal of Science, 2024)
The results of this study indicated that the the average number of 2nd and 3rd instars of dubas.nymphs Ommatissus lybicus DeBerg. were consumed by Chrysoperla mutata MacL. larvae were 291.4 . The percentage of consumption were 9.13,29.34 and 61.53% for 1st ,2nd and 3rd instar larvae respectively.